High correlation in antibody titers between the Sabin-Feldman dye test and an enzyme-linked immunosorbent assay detecting immunoglobulin G antibodies to the nucleoside triphosphate hydrolase of Toxoplasma gondii. - Asai, T (1992)
An enzyme-linked immunosorbent assay to detect immunoglobulin G antibodies against nucleoside triphosphate hydrolase, which is a specific and dominant antigen of Toxoplasma gondii, was developed, and the sensitivity and specificity of the test were compared with those of the Sabin-Feldman dye test. One hundred percent agreement was observed in comparative study between those tests on 37 positive and 50 negative human sera. Antibody titers in the enzyme-linked immunosorbent assay test, which were expressed as the reciprocal of the highest positive dilution of serum, were just 100 times those in the dye test on 81% (30 of 37) of the positive sera.